Excerption and inclusion in language and architecture - Emad Younis Lafi (Iraqi Journal of Architecture and Planning, 2009)
Excerption and inclusion are two terms in Arabi; rhetoric. The excerption is defined as a taking apart oftext from Holly Quran or Hadith and put it in a poem, verse line, or put it in a prose texr.But the Iinguistics expand the concept of this term to include taking from anolher sciences andknowledge, like Grammar, Philology, and Proso.lr,.Inclusion is defined as taking a verse line or part of verse line from another poet to put it in anew poem, it is necessary that the poet who take the text should declare it, and if he hrdes it, itwill be plagiarism.This search is use these two terms in iirchitecture, we have now new two terms inarchitecture, first one; architectural excerption. it means the designer takes a part of religious orhistorical building and put it in his new design. The designer also can take from another sciencesand knowledge, like physics, mathematics. or schools of modern criticism like deconstruction, toput his new design. The second lerm (architectural inclusion) means the designer takes a part ofanother modem design, neither religious nor historical, if he hides this. it is consi(lered asarchitectural plagiarism.The search proved that there are many architectural designs lvhich include the nreaning olthese two terms.